Diagnostic accuracy of axillary nodal ultrasound after neoadjuvant chemotherapy in node-positive breast cancer patients: A validation study - Syeda Sakina Abidi; Lubna Mushtaque Vohra; Asad Ali Kerawala; Imrana Masroor; Muhammad Umair Tahseen (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the accuracy and false negative rate of axillary ultrasound compared to sentinel node biopsy. Method: The retrospective study was conducted at the Aga Khan University Hospital, Karachi, from February 1 to March 31, 2021, and comprised data of breast cancer patients who had undergone neo-adjuvant chemotherapy followed by axillary lymph node dissection or axillary disease diagnosed using lymph node biopsy or sentinel lymph node biopsy between January 1, 2016, and December 30, 2020. After receiving neoadjuvant chemotherapy, axillary ultrasound findings were compared with histopathology of lymph nodes. Data was analysed using SPSS 22. Results: Of the 155 patients evaluated, 104(67.1%) were diagnosed with negative axillary lymph nodes and 51(32.9%) were diagnosed with positive axillary lymph nodes post-chemotherapy. The overall mean age was 51.13±1.3 years. When histopathology results were compared with those of axillary ultrasound, 36 cases turned out to be true positive, while 23(%) were false negative, yielding a positive predictive value of 75% and negative predictive value of 65%. Axillary ultrasound had 75% accuracy, false negative rate 30%, sensitivity 61% and specificity 84.4%. Conclusion: Axillary ultrasound was found to be fairly useful, but not completely reliable, in identifying positive lymph nodes, Continuous...